THE INFLUENCE OF REFERENCE GROUPS, PRODUCT QUALITY, AND AFTER SALES SERVICE ON THE PURCHASE DECISION OF YAMAHA BRAND MOTORCYCLES (CASE STUDY IN THE COMMUNITY OF PINO RAYA DISTRICT, BENGKULU CITY) - Bima Akbar Ganatal; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
This study aims to analyze the influence of reference groups, product quality, and after-sales service on purchasing decisions for Yamaha brand motorcycles in Pino Raya District, Bengkulu City. The study used a quantitative method with a sample of 160 respondents selected by Accidental Sampling. The data analysis technique used was multiple linear regression. The results of the study showed that partially, reference groups, product quality, and after-sales service had a positive and significant effect on purchasing decisions. The regression coefficient value for the reference group was 0.561, product quality 0.289, and after-sales service 0.412. Simultaneously, the three variables contributed 39.9% to purchasing decisions, while welfare was influenced by other factors outside this study. These results indicate the importance of a marketing strategy that strengthens the role of reference groups, maintains product quality, and optimizes after-sales service to improve consumer purchasing decisions.